Clinical Outcome Patterns of Use of Radium-223 in Patients with Metastatic Castration-Resistant Prostate Cancer - Colleen Mackenzie; Jasna Deluce; Morgan Black; Emma Churchman; Eric Winquist; Scott Ernst; David T. Laidley; Matthew Parezanovic; Kylea Potvin; Ricardo Fernandes (Current Oncology)
Introduction: Radium-223 dichloride (radium-223) is a bone-targeting radioisotope therapy that aids in the survival of patients with metastatic castration-resistant prostate cancer (mCRPC) to bones. This study aimed to describe the clinical characteristics and outcomes of patients with mCRPC treated with radium-223 in a real-world setting. Methods: This was a retrospective study of patients with mCRPC treated with radium-223 between 2016 and 2020 at the London Health Sciences Centre in London, Canada. The baseline characteristics between the patients receiving 1–3 and 4–6 treatment cycles were compared using a two-sample t-test and Chi-square test. ANOVA was used to determine if there was a difference in each diagnostic variable per treatment cycle. Kaplan–Meier curves were generated to estimate progression-free survival (PFS) and overall survival in the patients treated with different numbers of cycles. Results: Fifty eligible patients were identified. The median age was 71 years (IQR: 66–76). Most patients (62%) received radium-223 beyond the third-line treatment. The mean number of radium-223 treatments was four. While 60% of the patients received 4–6 injections, 40% received 1–3 injections. Fifty-eight percent (58%) of the patients demonstrated a clinical benefit, with the remainder expressing either disease progression (28%) or stable disease (10%). The patients treated with 4–6 cycles had a delay to disease progression compared to those given 1–3 cycles of radium-223 (F5,35 = 10.52, p < 0.001). A higher alkaline phosphatase level prior to treatment was associated with a longer PFS (z33 = 2.362, p = 0.018). Treatment-related hospitalization for skeletal-related events was noted in 8% of the patients, and 14% required treatment discontinuation due to hematologic toxicity. Conclusions: This study confirms the safety of radium-223 in patients with mCRPC in a real-world setting. The radium-223 treatment was associated with a clinical benefit in the majority of the patients, particularly in those with higher pre-treatment serum alkaline phosphatase levels. Further studies to identify the predictive biomarkers are warranted to better guide the contemporary use of radium-223.